Genetic population structure and variation at phenology‐related loci in anadromous Arctic char (Salvelinus alpinus). Issue 1 (3rd October 2019) - Madsen, Rikke P. A.; Jacobsen, Magnus W.; O'Malley, Kathleen G.; Nygaard, Rasmus; Præbel, Kim; Jónsson, Bjarni; Pujolar, Jose M.; Fraser, Dylan J.; Bernatchez, Louis; Hansen, Michael M.
Abstract: The Arctic will be especially affected by climate change, resulting in altered seasonal timing. Anadromous Arctic char ( Salvelinus alpinus ) is strongly influenced by sea surface temperature (SST) delimiting time periods available for foraging in the sea. Recent studies of salmonid species have shown variation at phenology‐related loci associated with timing of migration and spawning. We contrasted genetic population structure at 53 SNPs versus four phenology‐related loci among 15 anadromous Arctic char populations from Western Greenland and three outgroup populations. Among anadromous populations, the time period available for foraging at sea (>2°C) ranges from a few weeks to several months, motivating two research questions: (a) Is population structure compatible with possibilities for evolutionary rescue of anadromous populations during climate change? (b) Does selection associated with latitude or SST regimes act on phenology‐related loci? In Western Greenland, strong isolation by distance at SNPs was observed and spatial autocorrelation analysis showed genetic patch size up to 450 km, documenting contingency and gene flow among populations. Outlier tests provided no evidence for selection at phenology‐related loci. However, in Western Greenland, mean allele length at OtsClock1b was positively associated with the time of year when SST first exceeded 2°C and negatively associated with duration of the period where SST exceeded 2°C. This is consistent with local adaptation for making full use of the time period available for foraging in the sea. Current adaptation may become maladaptive under climate change, but long‐distance connectivity of anadromous populations could redistribute adaptive variation across populations and lead to evolutionary rescue.